Ownership dynamics in local multi-stakeholder initiatives. Issue 9 (2nd September 2018) - Biekart, Kees; Fowler, Alan
Abstract: The nature and dynamics of ownership are often neglected features of multi-stakeholder initiatives (MSIs). Seventeen cases in four countries illustrate characteristics of narrow government or broad societal ownership and forces for change over time. Refinements to the application of Gaventa's Power Cube are used to analyse such shifts from the perspective of invited and closed spaces for participation. Observations about ways in which stakeholder groups can create a more enabling environment for their collaboration are discussed. Sensitivity to sub-national conditions by weaving endogenous and exogenous forces appears to be crucial if MSIs are to be effective vehicles of choice for implementing the Sustainable Development Goals.